Characteristics of Tapioca-Glucomannan Based Foam Biocomposites with Variations in Microcrystalline Cellulose Concentration and Gelatinization Stirring Time - Dewa Ayu Made Wulan Sintya Dewi; Amna Hartiati; Bambang Admadi Harsojuwono; Sri Suhartini (Green Engineering Society, 2026)
Biocomposites are materials composed of a combination of polymer matrices and natural reinforcing agents that are environmentally friendly and have the potential to replace non-biodegradable synthetic polymers. The development of biodegradable foam biocomposites represents an innovation in lightweight materials that can be applied as sustainable packaging. This study aimed to examine the effect of microcrystalline cellulose (MCC) concentration on the characteristics of foam biocomposites and to determine the optimal concentration to produce the best quality foam. The research employed a Randomized Block Design (RBD) with three MCC concentration treatments (1.5%, 3.5%, and 5.5%) across three gelatinization times (1 minute, 2 minutes, and 3 minutes). The observed variables included tensile strength, density, tear resistance, compression set, thickness, swelling, elongation at break, and biodegradation time. The data were analyzed using Analysis of Variance (ANOVA) followed by the Honestly Significant Difference (HSD) test. The results showed that MCC concentration and gelatinization time significantly affected tensile strength, density, tear resistance, compression set, thickness, swelling, elongation at break, and biodegradation time. The best foam biocomposite was obtained at 5.5% microcrystalline cellulose concentration and 1 minute of gelatinization time, with tensile strength of 5.04 N/cm², density of 0.38 g/cm³, tear resistance of 3.60 N/cm², compression set of 19.99%, thickness of 15.11 mm, thickness swelling of 1.22%, elongation at break of 3.02%, and biodegradation time of 13 days.